Intermediation in Networks - Jan-Peter Siedlarek (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2014)
I study intermediation in networked markets using a stochastic model of multilateral bargaining in which traders compete on different routes through the network. I characterize stationary equilibrium payoffs as the fixed point of a set of intuitive value function equations and study efficiency and the impact of network structure on payoffs. There is never too little trade but there may be an inefficiency through too much trade in states where delay would be efficient. With homogenous trade surplus the payoffs for players that are not essential to a trade opportunity go to zero as trade frictions vanish.
Keywords: C73; C78; L14; 330; bargaining; financial networks; intermediation; matching; middlemen; networks; over-the-counter markets; stochastic games